Impact of a guaranteed annual income program on Canadian seniors’ physical, mental and functional health - McIntyre, Lynn (Can J Public Health, 2016)
OBJECTIVE: Although there is widespread recognition that poverty is a key determinant of health, there has been less research on the impact of poverty reduction on health. Recent calls for a guaranteed annual income (GAI), defined as regular income provided to citizens by the state regardless of work status, raise questions about the impact, relative to the costs, of such a population health intervention. The objective of this study was to determine the impact of Canadian seniors’ benefits (Old Age Security/Guaranteed Income Supplement, analogous to a GAI program) on the self-reported health, self-reported mental health and functional health of age-eligible, low-income seniors. METHODS: We used the 2009–2010 Canadian Community Health Survey to examine unattached adult respondents with an annual income of $20,000 or less, stratified by seniors’ benefits/GAI eligibility (55–64 years: ineligible; 65–74 years: eligible). Using regression, we assessed self-reported health, self-reported mental health and functional health as measured by the Health Utilities Index, as outcomes for seniors’ benefits/GAI-eligible and -ineligible groups. RESULTS: We found that individuals age-eligible for seniors’ benefits/GAI had better health outcomes than recipients of conditional income assistance programs. Eligibility for seniors’ benefits/GAI after age 64 was associated with better self-reported health, functional health and self-reported mental health outcomes, and these effects were observed until age 74. CONCLUSION: Using seniors’ benefits as an example, a GAI leads to significantly better mental health and improved health overall. These improvements are likely to yield reduced health care costs, which may offset the costs associated with program expansion.